Wisdom of God as Ars Dei Have bl. Augustine: between Neoplatonism and Christianity - Fokin Aleksei (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2016)
The article deals with the notion of ars Dei (“art of God”) in philosophical and theological thought of St. Augustine of Hippo. It is argued that ars Dei is not only an intelligent design or knowledge which God had with regard to his creation, but also the divine Wisdom and Word of God, in whom exist the eternal and unchangeable forms and reasons of all things, according to which God not only knows, but also creates everything. It is notiﬁed, that the notion of ars Dei reﬂects the Neo-Platonic notion of the universal Intellect (νοDς) and also has an aﬃ nity with the concept of the universal Logos, or “designing Logos” (τεχνικOς λMγος), as found in the works of Philo and in those of several Greek Fathers of the Church, as well as is a result of a development of the biblical notions of the Wisdom and Word of God, through whom all things were made. In the same time Augustine’s doctrine is truly without peer in contemporary philosophical and Patristic literature.